2020
DOI: 10.1111/jch.14141
|View full text |Cite
|
Sign up to set email alerts
|

India Hypertension Control Initiative—Hypertension treatment and blood pressure control in a cohort in 24 sentinel site clinics

Abstract: The India Hypertension Control Initiative (IHCI) is a multi‐partner initiative, implementing and scaling up a public health hypertension control program across India. A cohort of 21,895 adult hypertension patients in 24 IHCI sentinel site facilities in four Indian states (Punjab, Madhya Pradesh, Maharashtra, and Telangana), registered from January 2018 until June 2019 were assessed at baseline and then followed up for blood pressure (BP) control and antihypertensive medication use. Among all registrations, 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 12 publications
3
30
0
Order By: Relevance
“…67 The previous meta-analysis from India reported significant differences in rural and urban on awareness and control levels while no significant difference was noted for percentage treated. 61 In our review we found two studies that reported no difference between urban and rural population while four studies reported rural populations to have poorer control.…”
Section: Discussionmentioning
confidence: 80%
“…67 The previous meta-analysis from India reported significant differences in rural and urban on awareness and control levels while no significant difference was noted for percentage treated. 61 In our review we found two studies that reported no difference between urban and rural population while four studies reported rural populations to have poorer control.…”
Section: Discussionmentioning
confidence: 80%
“…29 However, the India Hypertension Control Initiative – a programme supported by the government and WHO – which includes opportunistic screening at public primary care and lower secondary care facilities was launched in only five states in 2017. 30 Our estimates point to the potential impact of such a programme and give urgency to plans to implement it in all states by 2023. The results also suggest that the impact would be even greater if private facilities also implemented screening or if people shifted their health-care utilization towards the public sector.…”
Section: Discussionmentioning
confidence: 90%
“…However, the India Hypertension Control Initiative (IHCI) was launched—in 5 states—only in November 2017. An observational study found that BP control achieved by public health facility patients increased from 26% at registration in the IHCI to 60% at follow-up [ 26 ]. Our findings can help identify states and sociodemographic groups to be targeted as this program is rolled out over the country.…”
Section: Discussionmentioning
confidence: 99%